Smart Trash Can Using Ultrasonic Infrared Sensor and Touch Sensor Based on Arduino Mega - Tullah, Rahmat; Saputri, Fiqih Hana; Syahrin, Alvi (JURNAL SISFOTEK GLOBAL, 2024)
Most of the trash bins at school are conventional models. When you want to dispose of trash you have to open or push the lid on the trash can, sometimes the lid is dirty with garbage piling up because the cleaners rarely check the condition of the trash can, this makes students' interest and awareness low to throw garbage in place. The purpose of this research is to design a tool that can facilitate and attract students' interest in disposing garbage in its place and making it easier for janitors to check and control the contents of the waste. This research make the environment at SMK Yaspih Rajeg cleaner because most students are no longer lazy and hesitant to throw garbage in its place, supported by the performance of cleaners who are more optimal in checking and controlling the contents of the trash. This study uses several methods such as data collection and analytical methods (Structured Analysis and Design) with flowcharts. The result, smart trash can that uses Arduino Mega as a microcontroller combined with several sensors and modules such as ultrasonic sensors, infrared sensors, touch sensors, servo motors, and SIM800l V2 which presents various features in smart trash cans.